2021
DOI: 10.1021/jacs.1c00886
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Selective Aza-Pinacol Coupling via Atom Transfer Catalysis

Abstract: A cross-selective aza-pinacol coupling of aldehydes and imines has been developed to afford valuable β-amino alcohols. This strategy enables chemoselective conversion of aliphatic aldehydes to ketyl radicals, in the presence of more easily reduced imines and other functional groups. Upon carbonyl-specific activation by AcI, a photoinitiated Mn catalyst selectively reduces the resulting α-oxy iodide by an atom transfer mechanism. The ensuing ketyl radical selectively couples to imines, precluding homodimerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 51 publications
(84 reference statements)
0
25
0
Order By: Relevance
“…6,7 Stereoselective delivery of carbanions or radicals to imines, oximes, and hydrazines derived from ketones is an attractive strategy for preparing αtertiary amines (Figure 1a). 8,9 Small molecule catalysts struggle to control facial delivery of reactive intermediates because of the small steric and electronic differences between the two substituents on the prochiral carbon, resulting in relatively few examples of asymmetric catalytic radical hydroalkylation of aldimines and, to our knowledge, no catalytic hydroalkylations of ketimine congeners. 10 Enzymes are ideal for this challenge; however, natural biocatalytic methods involving additions to imine congeners are rare.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Stereoselective delivery of carbanions or radicals to imines, oximes, and hydrazines derived from ketones is an attractive strategy for preparing αtertiary amines (Figure 1a). 8,9 Small molecule catalysts struggle to control facial delivery of reactive intermediates because of the small steric and electronic differences between the two substituents on the prochiral carbon, resulting in relatively few examples of asymmetric catalytic radical hydroalkylation of aldimines and, to our knowledge, no catalytic hydroalkylations of ketimine congeners. 10 Enzymes are ideal for this challenge; however, natural biocatalytic methods involving additions to imine congeners are rare.…”
mentioning
confidence: 99%
“…Strategies for preparing α-secondary amines are well developed with frequent application of asymmetric reduction of imines and enamines, as well as biocatalytic transamination and reductive amination . In contrast, strategies for preparing enantioenriched α-tertiary amines remain underdeveloped and desired for drug design and natural product synthesis. , Stereoselective delivery of carbanions or radicals to imines, oximes, and hydrazines derived from ketones is an attractive strategy for preparing α-tertiary amines (Figure a). , Small molecule catalysts struggle to control facial delivery of reactive intermediates because of the small steric and electronic differences between the two substituents on the prochiral carbon, resulting in relatively few examples of asymmetric catalytic radical hydroalkylation of aldimines and, to our knowledge, no catalytic hydroalkylations of ketimine congeners . Enzymes are ideal for this challenge; however, natural biocatalytic methods involving additions to imine congeners are rare. , We hypothesized that substrate promiscuous enzymatic platforms are competent catalysts for non-natural reaction mechanisms that address this challenge …”
mentioning
confidence: 99%
“…Instead, we were cognizant that acyl chloride (AcCl) readily adds to carbonyls, yielding stable α-acyloxy halides, even with enolizable aldehydes ( 30 ). We previously showed that acyl iodide (AcI) adducts of carbonyls enable distinct ketyl radical reactivity by atom- or electron-transfer reduction mechanisms ( 31 , 32 ). By contrast, we hypothesized that the more stable pivaloyl chloride (PivCl) adduct A may prevent the radical pathway and permit chemoselective formation of α-acyloxy Zn carbenoid B ( 33 ).…”
mentioning
confidence: 99%
“…Here, PIDA serves as a decarboxylative reagent and as a source of iodonitrene, promoting electrophilic amination of the resulting imine, which gives a diazirine after oxidative cleavage of the iodine species. Inspired by these elegant synthetic methods and our long-term interest in both catalytic [3 + 2] cycloaddition reactions , and hypervalent iodine­(III) chemistry, we were curious about the potential outcomes of the electrophilic amination of pyrrolidines using iodonitrene, which has not been documented (Figure D). Here, we report a mild and efficient method for the highly stereoselective synthesis of cyclobutanes carrying diverse functionalities with different substitution patterns from readily accessible pyrrolidines using iodonitrene chemistry.…”
mentioning
confidence: 99%